Morpho-semantic analysis of ambiguous morphemes in Chinese compound word recognition: An fMRI study. (16th July 2021) - Zhao, Simin; Wu, Yan; Tsang, Yiu-Kei; Sui, Xue; Zhu, Zude
Abstract: The present fMRI study examined the neural basis of processing context-supported or -unsupported interpretations of ambiguous morphemes during Chinese compound word reading in a masked priming lexical decision task. Targets were Chinese bimorphemic words that contained ambiguous morphemes. Prime words contained the same ambiguous morphemes with either the same meanings (context-supported interpretation) or different ones (context-unsupported interpretation). Lexical-level semantic sharing and unrelated control conditions were also included. Compared to the unrelated control condition, the context-supported morphemic meaning was associated with increased activity in the left SFG and bilateral MTG, and this priming effect could be dissociated from that of the lexical-level semantic-related condition. In broader brain regions, including the left SFG, bilateral MTG, left STG, right IOG, and left precuneus, the context-unsupported meaning condition showed decreased activity compared with the unrelated control condition. These findings indicate that both the context-supported and -unsupported meanings evoke significant priming effects, however, they differ from each other with different brain basis, providing new insight into the neural substrates of ambiguous morpheme processing. Highlights: Left SFG and bilateral MTG are core brain regions in ambiguous morpheme processing. Each distinct morphemic meaning of ambiguous morphemes has independent neural entry. Contextual information would modulate the activation pattern of each interpretation of ambiguous morphemes.